Effect of intrinsic and extrinsic foot muscle strengthening exercises on foot parameters and foot dysfunctions in pregnant women: a randomised controlled trial. (2nd February 2019) - Ramachandra, Preetha; Kumar, Pratap; Kamath, Asha; Maiya, Arun G
Abstract : Background/Aims: The medial longitudinal arch of the foot is supported by both active and passive systems. Focusing on the active system by strengthening the intrinsic and extrinsic foot muscles and its effect on the foot parameters in pregnant women has been underresearched. Methods: A total of 86 primigravidae (women who were pregnant for the first time) were recruited at the 18 th week of gestation. The control group received routine antenatal exercises and the study group received intrinsic and extrinsic foot exercises along with the routine antenatal exercises. The outcome measures evaluated were foot parameters and foot dysfunctions, which were reassessed at the 24 th and 32 nd week of gestation. Results: The results suggested that there was a significant difference between the study group and control group in terms of foot width, navicular height, truncated foot length and normalised navicular height truncated, which indicated that there was a significant drop in the arch of the foot (pronation) in the control group compared to the study group ( P =<0.001). The foot dysfunctions reported by the study group were significantly less compared to the control group. Conclusions: A comprehensive foot exercise programme was found to be effective in reducing the drop in arch height and also in preventing foot dysfunctions in pregnant women.